1987
DOI: 10.1002/bies.950070305
|View full text |Cite
|
Sign up to set email alerts
|

Desmutagens and bio‐antimutagens – their modes of action

Abstract: SummaryThere are two ways of preventing induced cellular mutagenesis. In the first, mutagens are inactivated by ' desmutagens' before they can attack the DNA. In the second, ' bio-antimutagens' interfere with cellular $xation processes working on damage in DNA. Examples of modes of action are shown for these inhibitors of induced mutations and implications for reducing genetic damage in man are discussed. lntroduct ion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
8

Year Published

1990
1990
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 16 publications
0
61
0
8
Order By: Relevance
“…Desmutagenic substances can prevent the action of damage-inducing agents by adsorbing to them. Bioantimutagenic agents can act in injury prevention or DNA repair (Kada and Shimoi, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Desmutagenic substances can prevent the action of damage-inducing agents by adsorbing to them. Bioantimutagenic agents can act in injury prevention or DNA repair (Kada and Shimoi, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Desmutagenic substances are capable of blocking damage-inducing agents mainly by adsorbing them, and they largely act in the extracellular environment. Bioantimutagenic agents are capable of damage prevention or work at the level of DNA repair, acting within the cell (Kada and Shimoi, 1987). De Flora (1998) has also suggested that bioantimutagenic substances act as modulators of repair and DNA replication, stimulate the errorfree repair pathway in DNA damage, or inhibit the repair systems subject to error.…”
Section: Discussionmentioning
confidence: 99%
“…Desmutagenic substances are able to block the action of DNA damage-inducing agents, mainly by their adsorption, acting preferentially in extracellular medium. On the other hand, bioantimutagenic agents are those capable of exerting their effect by preventing DNA lesions or promoting DNA repair, thus acting inside the cell (Kada and Shimoi, 1987). The bioantimutagenic substances act as modulators of DNA replication and repair, stimulate error-free repair of DNA damage, or inhibit repair systems that are subject to error (De Flora 1998;Oliveira et al, 2006).…”
Section: Experimental Group Mn Frequency Means ± Se Dr%mentioning
confidence: 99%